Pyrolysis kinetic study of cathode material derived from spent lithium ion batteries (LIBs): Comparison of different models. (3rd July 2021) - Yu, Shaoqi; Zhang, Baogui; Xiong, Jingjing; Yao, Zhitong; Wu, Daidai; Liu, Jie; Xu, Shaodan; Tang, Junhong
ABSTRACT: Separating cathode material and Al foil from spent lithium-ion batteries (LIBs) is a critical step for LIBs recycling. As compared to chemical dissolving and decomposition, the pyrolysis pretreatment is an alternative and simple method. In this work, the pyrolysis kinetics of cathode material were comparatively studied using various isoconversional methods, including Flynn-Wall-Ozawa (FWO), Friedman, Kissinger-Akahira-Sunose, Starink, Tang, and Boswell. The thermal degradation mechanism was investigated by the Coats-Redfern (CR) and master-plot methods as well. The thermogravimetric analysis revealed that cathode material decomposition could be divided into three stages with mass losses of 1.51%, 0.787%, and 0.449%, respectively. Activation energy (E α ) calculated using the six model-free methods showed a similar trend, gradually increasing as the degree of conversion ( α ) increased from 0.001 to 0.009, and then significantly elevating. The FWO method gave the best fitting and Eα values first increased from 12.032 to 24.433 kJ·mol −1 with α elevating from 0.001 to 0.009, then increased further to 43.187 kJ·mol −1 . Both CR and Criado methods indicated that the degradation of cathode material can be explained by the diffusion models. Implications : The rapid growth in the production and consumption of lithium-ion batteries (LIBs) for portable electronic devices and electric vehicles has resulted in an increasing number of spent LIBs. Thermal treatment offers advantages of high-efficiency and simple operation. Understanding the thermal process of spent LIBs and probing its kinetic are significant for the large-scale treatment. Through this study, it will be significant for the reactor designing and optimizing in practice.